Improving the performance of Mobile Wireless Sensor Networks using modified DBSCAN - Gupta, Abhinav; Singh, Prabhdeep (International Journal of Computer Sciences and Engineering, 2025)
In wireless sensor networks the nodes are most of times static in nature. But in Mobile wireless sensor networks the nodes are mobile in nature, in such kind of networks if the emphasis is given on the clustering then the cluster head sometimes tend to move out of the cluster. The paper analyzes ECBR-MWSN which takes into account mobility, remaining energy and distance to the base station while making selection for the cluster head nodes. The proposed work however has tried to reduce the time taken in rotation of cluster heads. The performance of network was analyzed using throughput, delay and packet delivery ratio which showed a significant improvement.